Co-Triggering of Diseases During Transitional Period in Dairy Animals of Punjab - Thakur, Niharika; Singh, Parminder; Kasrija, Rajesh (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The present study was undertaken to determine the predisposition of one transitional disease on the other in various dairy animals of Punjab. For this purpose, a total of 250 respondents were randomly selected and were interviewed personally from various parts of Punjab through a structured interview schedule. Among the various transitional diseases in dairy farms, anoestrus was found to be high (59.00%) followed by mastitis (52.00%). Dystokia was found to be highly significant (p<0.01) with transitional diseases such as Retention of Placenta (ROP) and metritis. ROP had highly significant variation (p<0.01) with diseases such as dystokia, mastitis, ketosis and metritis. Anoestrus was found to be significant (p<0.05) with repeat breeding. Ketosis was found to be highly significant with anoestrus (p<0.01). Milk fever varied significantly with dystokia and ROP (p<0.05). Metritis had significance with dystokia, mastitis, anoestrus and milk fever (p<0.01). Also, repeat breeding was highly significant (p<0.01) with mastitis. Thus, it was concluded that presence of one transitional disease can predispose the dairy animal to other transitional diseases as well. Hence, farmers are educated on transitional disease management through training and other extension and advisory services.